Heparin molecularly imprinted surfaces for the attenuation of complement activation in blood. (14th August 2015) - Rosengren-Holmberg, Jenny P.; Andersson, Jonas; Smith, James R.; Alexander, Cameron; Alexander, Morgan R.; Tovar, Günter; Ekdahl, Kristina N.; Nicholls, Ian A.
<x xml:space="preserve">Abstract</x> Heparin molecularly imprinted polymer films limit complement activation in whole blood.